Transformational leadership, organizational support, and self-determination: impact on knowledge sharing in creative economy actors - Probosari, Ninik; Rahatmawati, Istiana; Ardhanariswari , Kartika Ayu (Jurnal Konseling dan Pendidikan, 2025)
The purpose of this study was to determine the effect of transformational leadership, perceived organizational support, and self-determination on knowledge-sharing behavior, with individual personality as a moderating factor, among creative economy actors. Recognizing the importance of knowledge sharing in fostering innovation and collaboration within the creative economy, this research aimed to explore how leadership styles and organizational support influence individuals’ willingness to share knowledge. This study employed a quantitative research design and was conducted at X, focusing on a population of creative economy actors within the organization. To gather data, a purposive sampling technique was utilized, resulting in a sample of 100 respondents who were selected based on specific criteria relevant to the study. This approach ensured that the participants had the necessary experience and insights related to the constructs being examined. The data analysis technique employed in this study was Partial Least Squares (PLS), a statistical method suitable for modeling complex relationships among variables. PLS allows for the assessment of both measurement and structural models, providing a comprehensive understanding of the relationships between transformational leadership, perceived organizational support, self-determination, and knowledge-sharing behavior. The findings of this study are expected to contribute to the existing literature on leadership and knowledge management within the creative economy, offering valuable insights for practitioners aiming to enhance knowledge-sharing practices. By highlighting the role of individual personality as a moderating factor, this research may also inform strategies for fostering a collaborative environment that encourages knowledge exchange among creative economy actors.